An outline of achievements in selected areas of forest research in Ireland 1960–2021 - N. Farrelly; M. Nemesio-Gorriz; I. Short; Á. Ní Dhubháin; B. Tobin; R. O’Hanlon; R. Earl; A. McCullagh; C. O’Donoghue; M. Ryan (Irish Journal of Agricultural and Food Research, 2022)
In this paper, we provide an overview of achievements in forest research in Ireland carried out by various agencies over the past 60 yr. Many of the outcomes of the research have ensured that policy and practice are well-founded, and many of the research results form the basis of current forest standards and practice. Forest research has, and will continue to have, a significant role in national policy development and international reporting commitments. The achievement of future goals and targets is increasingly dependent on the maintenance of the goods and services that forests provide; these can be enhanced through the establishment of new forests and by appropriate management of the resource (e.g. The EU Green Deal and EU Forest Strategy). We outline the current state of knowledge which can be used to inform afforestation goals and the importance of tree improvement, forest management and forest protection to improve competitiveness and sustainability. Research into forestry and carbon provides a focus on the opportunities and challenges of climate change to Irish forestry. Future efforts will involve longer-term monitoring of environmental change commensurate with the forest rotation to reduce the uncertainties associated with climate change. Research into forestry economics, attitudinal surveys and behavioural studies may help inform the achievement of future policy goals. Reducing the impacts of biotic attack through efficient surveying, disease monitoring and assessing future risk is likely to be the focus of future research effort.